PELAKSANAAN PEMBERIAN INFORMED CONSENT DAN KELENGKAPAN INFORMASI DI RSU JATI HUSADA KARANGANYAR TAHUN 2014 - Sekar Arum Kencananingtyas; Tri Lestari; - Harjanti (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2014)
ABSTRACTHospitals Jati Husada Karanganyar on providing information relating to informed consent is not informative.In because patients who will be there are 2 types of medical treatment that the patient and the patient’s generalpatient One Day Care (ODC). For a general explanation of the patient while the patient information clearerOne Day Care (ODC) provision of information only described in general terms. The purpose of this study wasto determine the implementation of the provision of informed consent and completeness of information thatcovers 6 main topics, namely Diagnosis of disease, objective, risk measures, risk of complications, alternativeactions, Prognosis. This type of research is descriptive qualitative and quantitative. This study used interviewsand observation guidelines. Qualitative data processing techniques with Data Reduction (Data Reduction),Presentation of Data (Data Display), Consclusion Drawing / Quantitative verivication while the collection(Collecting), and Presenting (Narrative) or presentation of data, analysis of the data used is descriptivequalitative and quantitative analysis . The results show the implementation of the provision of informed consentafter receiving clear information from the initial patients in the emergency room entrance and approve medicaltreatment by signing an informed consent to complete the service. Informed Consent form filling completenesslowest identification on No.KTP / SIM 15 (100%) incomplete and type of information conveyed by the highestdoctor medical treatment 15 (100%). Hospitals are advised Hospitals Jati Husada Karanganyar have fixedprocedures on patient care procedures One Day Care (ODC) and design in a revised informed consent formaccording to standard hospital care with a minimum of information includes the type of diagnosis (WD /DD), Primary Diagnosis, Medical Action, Indication actions, Procedures, Objectives, Risks, Complications,Prognosis, and Risk Alternative formats are based on the Indonesian medical counsil.Keyword: Informed Consent, Completeness of informationABSTRAKRSU Jati Husada Kabupaten Karanganyar pada pemberian informasi yang berkaitan dengan informed consentbelum informatif. Di karenakan pasien yang akan dilakukan tindakan medis ada 2 jenis pasien yaitu pasien umumdan pasien One Day Care (ODC). Untuk pasien umum penjelasan informasi lebih jelas sedangkan pasien OneDay Care (ODC) pemberian informasi hanya dijelaskan secara umum saja. Tujuan dari penelitian ini adalahmengetahui pelaksanaan pemberian informed consent dan kelengkapan informasi yang mencakup 6 hal pokokyaitu Diagnosa penyakit, Tujuan, Risiko tindakan, Risiko komplikasi, Alternatif tindakan, Prognosis. JenisPenelitian ini adalah deskriptif kualitatif dan kuantitatif. Penelitian ini menggunakan pedoman wawancara danpedoman observasi. Teknik pengolahan data kualitatif dengan Reduksi Data (Data Reduction), Penyajian Data(Data Display), Consclusion Drawing/verivication sedangkan Kuantitatif dengan Pengumpulan (Collecting),dan Memaparkan (Narasi) atau penyajian data, analisis data yang digunakan adalah analisis deskriptif kualitatifdan kuantitatif. Hasil penelitian menunjukkan pelaksanaan dalam pemberian Informed Consent setelahmendapatkan informasi yang jelas di UGD dari awal pasien masuk dan menyetujui tindakan medis denganmelakukan penandatanganan Informed Consent hingga selesai pelayanan. Kelengkapan formulir InformedConsent pengisian identifikasi terendah pada No.KTP/SIM 15 (100%) tidak lengkap dan Jenis informasi yangdisampaikan oleh dokter tertinggi yaitu tindakan medis 15 (100%).Disarankan RSU Jati Husada Karanganyarmemiliki prosedur tetap tentang prosedur pelayanan pasien One Day Care (ODC) dan desain formulir informedconsent di revisi sesuai standart pelayanan minimal rumah sakit dengan memuat jenis informasi tentangdiagnosis (WD/DD), Dasar Diagnosis, Tindakan Kedokteran, Indikasi Tindakan, Tata Cara, Tujuan, Risiko,Komplikasi, Prognosis, Alternatif dan Risiko yang berpedoman pada format Konsil Kedokteran Indonesia.Kata Kunci: Informed Consent, Kelengkapan Informasi